Marginal employment': stepping stone or dead end? Evaluating the German experience - Ronny Freier; Viktor Steiner (Institute for the Study of Labor (IZA), 2007)
Marginal employment', i.e. employment at low working hours and earnings not covered by social security, has been gaining importance in the German economy over the past decade. Using a large newly available panel data set and statistical matching techniques, we analyse the effects of marginal employment on future individual outcome variables such as unemployment, regular employment and earnings. In addition to average treatment effects, we calculate dynamic and cumulative treatment effects accounting for total time spent in various labor market states and related earnings over a period of three years. We find that marginal employment (i) does not affect time spent in regular employment within a three-years' observation period, (ii) reduces future unemployment, (iii) slightly increases cumulated future earnings, on average, and (iv) is associated with a small negative cumulative earnings effect for older workers in west Germany.
Keywords: J23; 330; Marginal employment; social security contributions; wage subsidies; labour market policy; evaluation of treatment effect; Arbeitsmarktpolitik; Ungeschützte Beschäftigung; Sozialversicherungsbeitrag; Lohnsubvention; Wirkungsanalyse; Beschäftigungseffekt; Deutschland